Penguatan Kapasitas Wali Asuh Melalui Layanan Bimbingan Konseling Berbasis Trilogi Dan Panca Kesadaran Santri Di Pondok Pesantren Nurul Jadid Paiton Pobolinggo - D'liya Camelia Putri, Juwita Ningsih, Agus Sulthoni Imami, Ummi Khairun Nikmah, Uswatun Hasanah, (Hidmah : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
This dedication is to find a model of strengthening the capacity of Foster Guardians through effective Guidance Counseling Services. Locus This research was conducted at foster care under the auspices of the Nurul Jadid Islamic Boarding School. In detail, the objectives of this study are 1) Description of the role of Foster Guardians at Nurul Jadid Islamic Boarding School, 2) Application of Counseling Guidance services at Nurul Jadid Islamic Boarding School, and 3) Analysis of Trilogy-based Counseling Guidance services and Santri's Five Consciousness at Nurul Jadid Islamic Boarding School. The method used was an initial assessment and collecting data by means of observation and interviews of foster students with purposive sampling, and analyzed by triangulation. The results of the Foster Care Service have an overview of the forms, themes, and strategies for guidance and counseling services based on the Trilogy and Five Awareness of the Santri so that they can become a basis for strengthening the capacity of guardianship, especially skills in alleviating daily problems, strengthening character, and a more inclusive Santri career orientation.